2001
DOI: 10.1046/j.1464-410x.2001.02258.x
|View full text |Cite
|
Sign up to set email alerts
|

Cimetidine in painful bladder syndrome: a histopathological study

Abstract: Objective To determine whether oral cimetidine, which reportedly improves symptoms in 60±70% of patients with painful bladder syndrome/interstitial cystitis has a similar mechanism of action on the human bladder and involving a similar peptidergic pathway as it has in human stomach, where it alters histamine-gastrin reactions mediated via H 2 receptors and a proton pump. Patients and methods Fourteen patients (13 women and one man, mean age 51 years) with refractory bladder pain and irritative urinary symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 10 publications
1
14
0
4
Order By: Relevance
“…The H2R antagonist cimetidine produced significant improvement in pain and nocturia in a limited trial of PBS patients [31]. Similar to our findings that PRV-induced pain mediated histamine is independent of TNF, symptom relief from cimetidine therapy was not associated with improved bladder pathology [39]. Pilot clinical studies yielded modest pain relief in IC patients receiving the old-line H1R antagonist hydroxyzine [40], but studies have not yet been conducted with newer generation H1R antagonists.…”
Section: Discussionsupporting
confidence: 76%
“…The H2R antagonist cimetidine produced significant improvement in pain and nocturia in a limited trial of PBS patients [31]. Similar to our findings that PRV-induced pain mediated histamine is independent of TNF, symptom relief from cimetidine therapy was not associated with improved bladder pathology [39]. Pilot clinical studies yielded modest pain relief in IC patients receiving the old-line H1R antagonist hydroxyzine [40], but studies have not yet been conducted with newer generation H1R antagonists.…”
Section: Discussionsupporting
confidence: 76%
“…Two very small observational trials 81,82 and one placebocontrolled RCT 83 have shown an improvement in symptoms of IC/BPS with cimetidine at various dosages. Thilagarajah et al 83 randomized 36 patients to cimetidine 400 mg orally twice daily vs. placebo and reported a significant improvement in symptoms in the cimetidine vs. placebo groups, respectively.…”
Section: Cimetidine (Option Grade B)mentioning
confidence: 99%
“…Atropine-resistant, ATP-mediated detrusor contractions have been shown to increase with age [42]. Histamine can evoke calcium transients in cultured human detrusor smooth muscle cells [43], and histamine receptors have been the target of IC therapy with H1 [44] or H2 [45] selective antihistaminics. Therefore, we routinely analyze the expression of muscarinic (M2, M3), purinergic (P2X1, P2X2, P2X3), and histamine (H1, H2) receptors in the detrusor smooth muscle cells by confocal immunofluorescence.…”
Section: Resultsmentioning
confidence: 99%